The Relationship between Body Fat Percentage and Physical Fitness: A Cross-Sectional Study among Medical Students in Indonesia - Batubara, Frisca Ronauli; Hendrika, Wendy; Prameswari, Shela A (Journal of Applied Nursing and Health, 2025)
Background: Physical fitness is the ability to carry out daily and leisure activities efficiently without excessive fatigue, thereby reducing the risk of chronic diseases. However, few studies in Indonesia have explored the link between body fat percentage and physical fitness among medical students. This study aims to analyze that relationship in students of the Faculty of Medicine, Indonesian Christian University. Methods: This observational cross-sectional study involved 57 university students selected using simple random sampling. Inclusion criteria were active medical students from the 2023 intake who were willing to participate. Exclusion criteria were students with musculoskeletal injuries or chronic diseases affecting physical performance. Body fat percentage was measured using skinfold calipers, and physical fitness was assessed using the Harvard Step Test. Data were analyzed using the Pearson correlation test. Ethical approval was obtained from the Health Research Ethics Committee of the Faculty of Medicine, Indonesian Christian University. Results: The analysis showed that the majority of students had a low physical fitness index, with 71.9% of participants having low physical fitness. A significant correlation was found between body fat percentage and physical fitness (p = 0.015), with increasing body fat percentage associated with decreased physical fitness. Conclusion: Increasing body fat percentage correlates with decreasing levels of physical fitness, suggesting that higher levels of body fat in college students are likely to negatively impact their ability to perform physical activity efficiently and reduce their risk of chronic disease.